PRIMARY EDUCATION IN INDIA : EXPERIENCES OF COMMUNITY PARTICIPATION - Dash, Ranjan Kumar; Panda, B.N. (THE PRIMARY TEACHER, 2010)
Education is a powerful instrument for social change, a means of reducing social inequalities and the most important investment in human resources. It is observed that the poor environment of the school, low performance of the learners, lack of monitoring and on-site support hamper the quality of education in schools. Article 45 of the Directive Principles of the State Policy in the Constitution states: ‘the state shall endeavour to provide free and compulsory education to all children upto the age of 14 years within 10 years of adoption of the Constitution’ (i.e. in 1950). It means that the goal of Universalisation of Elementary Education (UEE) was to be achieved in India by the end of 1960. However, the target of achieving UEE has been eluding the country till now. The National Policy on Education (NPE), 1986 and Programme of Action (POA) 1992 expressed its need very emphatically and planned to provide free and compulsory education of good quality to all children up to the age of 14 years by the turn of the twenty-first century.